2020
DOI: 10.1371/journal.pone.0243427
|View full text |Cite
|
Sign up to set email alerts
|

Impact of duration and magnitude of raised intracranial pressure on outcome after severe traumatic brain injury: A CENTER-TBI high-resolution group study

Abstract: Magnitude of intracranial pressure (ICP) elevations and their duration have been associated with worse outcomes in patients with traumatic brain injuries (TBI), however published thresholds for injury vary and uncertainty about these levels has received relatively little attention. In this study, we have analyzed high-resolution ICP monitoring data in 227 adult patients in the CENTER-TBI dataset. Our aim was to identify thresholds of ICP intensity and duration associated with worse outcome, and to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 34 publications
1
69
0
4
Order By: Relevance
“… 19 Although it must be acknowledged that ICP/CPP derangements in the historical cohort of these previous publications were much more prevalent than in our cohort, 19 potentially driving the PRx derangements seen. 27 , 46 , 52 , 53 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Although it must be acknowledged that ICP/CPP derangements in the historical cohort of these previous publications were much more prevalent than in our cohort, 19 potentially driving the PRx derangements seen. 27 , 46 , 52 , 53 …”
Section: Discussionmentioning
confidence: 99%
“…It can likely be attributed to brain volume loss at advanced ages, because brain atrophy does not allow for adequate swelling and generation of critical ICPs, which is a known driver of autoregulation failure in moderate/severe TBI. 27 , 46 , 52 , 53 …”
Section: Discussionmentioning
confidence: 99%
“…Other retrospective TBIicp analyses demonstrated that impaired CA reduces the tolerability for low CPP and high ICP. [18][19][20][21] On average, CPP targets <60 mm Hg were less common (10%; Fig. 2) compared to targets ‡70 mm Hg (55%; Fig.…”
Section: Precision Medicine In Tbimentioning
confidence: 99%
“…A signi cant reduction in ICP was reported in four studies which included ventriculostomy drainage prior to lumbar drainage [21,28,34,37], suggesting that ELD offers both a bene t when used as the sole modality of CSF diversion, and additional bene t when used in combination with EVD. Functional outcomes were not considered as a marker of "e cacy", rather ICP control can be considered as a surrogate marker of potentially improving functional outcome due to the association of intracranial hypertension and poor outcome [4]. The numbers enrolled in these combined studies are by far insu ciently powered to assess for an effect on functional outcome.…”
Section: E Cacymentioning
confidence: 99%